The variation in morphology of perennial ryegrass cultivars throughout the grazing season and effects on organic matter digestibility. (19th September 2013) - Beecher, M.; Hennessy, D.; Boland, T.M.; McEvoy, M.; O'Donovan, M.; Lewis, E.
Abstract The grass plant comprises leaf, pseudostem, true stem (including inflorescence) and dead material. These components differ in digestibility, and variations in their relative proportions can affect sward quality. The objective of this study was to determine the change in the proportion and organic matter digestibility (OMD) of leaf, pseudostem, true stem and dead components of four perennial ryegrass cultivars (two tetraploids: Astonenergy and Bealey and two diploids: Abermagic and Spelga) throughout a grazing season. The DM proportions and in vitro OMD of leaf, pseudostem, true stem and dead in all cultivars were determined during ten grazing rotations between May 2011 and March 2012. There was an interaction between rotation and cultivar for leaf, pseudostem, true stem and dead proportions. In May and June, Astonenergy had the highest leaf and lowest true stem proportion (P < 0·05). From July onwards, there was no difference in leaf or true stem proportion between cultivars. Bealey had the highest annual mean OMD (752 g kg−1) and Spelga the lowest (696 g kg−1; P < 0·05). The OMD followed the order leaf > pseudostem > true stem > dead. Bealey had the highest combined leaf and pseudostem proportion 0·92, which explains why it had the highest OMD. In this study, the tetraploid cultivars had the highest leaf and pseudostem proportion and OMD. For accurate descriptions of a sward in grazing studies and to accurately determine sward morphological composition, pseudostem should be separated from true stem, particularly during the reproductive stage when true stem is present.